Learning selection: a model for planning, implementing, and evaluating participatory technology development - Douthwaite, Boru; Park, J.; Keatinge, J.D.H. (2002)
This paper develops a model of the early adoption process that takes into account modifications made by users. The model is based on data from 13 attempts to introduce six postharvest technologies into the Philippines and Vietnam. It is built on an analogy between technology change and Darwinian evolution. At the core of the model is the interactive experiential learning process —learning selection (LS)— that is analogous to natural selection in the living world. In learning selection stakeholders engage with a new technology, individually playing the evolutionary roles of novelty generation and selection, and in their interactions creating recombinations of ideas and experiences and the promulgation of beneficial novelties. Peoples’ motivations to engage in learning selection, and its outcomes, are influenced by the interaction between their life worlds and their environments. The model has implications for management of agricultural technology change. It suggests the need for a nurturing of new technology during its early adaptation and adoption, until the point where the beneficiary stakeholders (manufacturers and users) are sufficiently numerous and have adequate knowledge to play the evolutionary roles themselves. The LS model, while developed with data from agro-mechanical technologies, could provide a theoretical underpinning for participatory technology development.